Pengaruh Komitmen Pimpinan dan Kompetensi Aparatur Terhadap Akuntabilitas Pengelolaan Barang Milik Daerah Kota Cimahi - Salsabila Ar-Ruum Sayoga; Ivan Yudianto (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The accountability of regional property management is something that must be proven in reality for the obligations carried out by the agency. Leadership commitment is one of the factors to realise the accountability of regional property management, for a high sense of involvement and loyalty to the organisation, the leader will obey the spoken commitment. Likewise, the competence of the apparatus seen from the ability, expertise, knowledge, and attitude of responsibility for their duties can realise the accountability of the management of regional property. The purpose of this study was to determine whether the Commitment of Leaders and Apparatus Competence to the Accountability of Regional Property Management in Cimahi City (Research on the Cimahi City Regional Work Unit). This research uses Quantitative Methods with descriptive and verification approaches (Path Analysis). The sampling technique used a saturated sample technique, obtained 30 respondents from each Cimahi City Regional Work Unit. Data collection was carried out by distributing questionnaires to the Head of Service as the Goods User and Employees who served as the Goods Manager of each Regional Work Unit. The results of this study indicate that, leadership commitment has a positive but insignificant effect on the accountability of regional property management, apparatus competence has a positive and significant effect on the accountability of regional property management, and leadership commitment has a positive but insignificant effect on the accountability of regional property management mediated through apparatus competence.